2010
DOI: 10.1063/1.3463379
|View full text |Cite
|
Sign up to set email alerts
|

Performance study of high operating temperature HgCdTe mid wave infrared detector through numerical modeling

Abstract: The design of present generation uncooled Hg1−xCdxTe infrared photon detectors relies on complex heterostructures with a basic unit cell of type ṉ+/π/p̱+. We present an analysis of double barrier ṉ+/π/p̱+ mid wave infrared (x=0.3) HgCdTe detector for near room temperature operation using numerical computations. The present work proposes an accurate and generalized methodology in terms of the device design, material properties, and operation temperature to study the effects of position dependence of carrier c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Internal radiative recombination is negligible in this case and contribution of reabsorption to net g-r process can be ignored at higher operating temperatures [15]. Our calculations in a previously published paper [13] showed that radiative g-r does not influence the model for non equilibrium mode reverse biased detectors. The relative contribution from the n + region diffusion current to the total reverse leakage current was calculated to be negligible, therefore total dark current is I total = I Auger + I SR + I TAT + I pdiff .…”
Section: Room Temperature I-v Analysismentioning
confidence: 74%
See 1 more Smart Citation
“…Internal radiative recombination is negligible in this case and contribution of reabsorption to net g-r process can be ignored at higher operating temperatures [15]. Our calculations in a previously published paper [13] showed that radiative g-r does not influence the model for non equilibrium mode reverse biased detectors. The relative contribution from the n + region diffusion current to the total reverse leakage current was calculated to be negligible, therefore total dark current is I total = I Auger + I SR + I TAT + I pdiff .…”
Section: Room Temperature I-v Analysismentioning
confidence: 74%
“…The dark I-V characteristics showed negative differential resistance at reverse bias in the homojunction devices. We have previously reported a one dimensional numerical device model for solution of carrier transport equations developed using finite difference method to describe the operation of these devices [13]. Using the same numerical method, we have modeled net thermal generation recombination (g-r) processes as sum of Auger, SRH and trap assisted tunneling (TAT) mechanisms on the right hand side of carrier continuity equations to simulate the experimental room temperature dark I-V characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The formulae to calculate all the basic material parameters such as bandgap, carrier mobility, intrinsic carrier concentration, effective masses and dielectric constants are well known and can be consistently found in literature [3]. All parameters used for our simulations can be found in ref 2.…”
Section: A Materials Parametersmentioning
confidence: 99%
“…A 1-D model has been used, which includes the electrical and optical properties of HgCdTe that are based on previously published models [6], [7]. In addition, Auger, SRH, and radiative G-R mechanisms have been included in the steady-state drift-diffusion model at all locations within the device.…”
Section: Device Design and Simulationmentioning
confidence: 99%